Persepsi nasabah terhadap kualitas pelayanan pada BMT yadika bangil - Anwar, Khoirul; Suriyok, Khamdan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The focus of this research is customer perceptions of service quality with a research focus on BMT Yadika Bangil. The purpose of this study was to determine how much service quality at BMT Yadika Bangil. This research method is descriptive quantitative, the subject of this research is the customer as the population. The sampling technique used is simple random sampling using Purposive sampling, with a total of 93 respondents. This research instrument uses primary data sources. From the theory according to Zeithaml. Parasuraman and Berry contain 5 indicators, namely reliability (X1), responsiveness (X2), confidence (X3), empathy (X4), and tangibles (X5). To analyze the data using a one-sample hypothesis test for the left side test. Based on the results of the study, the quality of BMT Yadika Bangil services is approaching the maximum. The calculation results state that from the expected value and quality of market service the t count > t table (6.05 > 1.66159) and is supported by the results achieved, namely 86.4 percent of the expected value.